Effect of the Interfacial Transition Zone on Basic Mechanical Properties of a Solid Composite Propellant - Shen, L.L.; Shen, Z.B.; Cui, H.R.; Li, H.Y.; Zhi, S.J. (Проблемы прочности, 2018)
The evaluation of basic mechanical properties are shown to be of importance for the solid composite propellant development and application. The numerical analysis approach termed the three-phase Voronoi cell finite element method, was proposed to evaluate of the interfacial transition zone effect. Numerical results showed that the performance of the effective modulus could be essentially enhanced by increasing the zone thickness. The module of the composite with the inhomogeneous zone was higher than that of the composite with the homogeneous one. The effect of different zones on volume fractions and matrix moduli was also calculated. The Voronoi method can also be helpful for analyzing the characteristic properties of other three-phase composites. Определение основных механических характеристик играет важную роль в разработке и применении композитного твердого ракетного топлива. Предложен численный метод, получивший название “трехфазный метод конечных элементов ячейки Вороного”, для оценки влияния зоны межфазного перехода. Численные результаты показывают, что эффективный модуль можно улучшить, увеличив толщину зоны межфазного перехода. Модуль композита с неоднородной зоной межфазного перехода выше такового с однородной зоной межфазного перехода. Рассчитано влияние различных зон межфазного перехода на объемные доли и модули матрицы. Для анализа характеристических свойств других трехфазных композитов также можно использовать трехфазный метод конечных элементов ячейки Вороного.